2011
DOI: 10.1016/j.bbamem.2010.11.025
|View full text |Cite
|
Sign up to set email alerts
|

The importance of bacterial membrane composition in the structure and function of aurein 2.2 and selected variants

Abstract: For cationic antimicrobial peptides to become useful therapeutic agents, it is important to understand their mechanism of action. To obtain high resolution data, this involves studying the structure and membrane interaction of these peptides in tractable model bacterial membranes rather than directly utilizing more complex bacterial surfaces. A number of lipid mixtures have been used as bacterial mimetics, including a range of lipid headgroups, and different ratios of neutral to negatively charged headgroups. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
82
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 87 publications
(84 citation statements)
references
References 81 publications
2
82
0
Order By: Relevance
“…This is consistent with the limited calcein release from PO lipid vesicles compared with DM vesicles, [1] and supports the conclusion of Cheng et al that PO vesicles are good model membranes to study these peptides. [6] …”
Section: Aureins Target the Bacterial Membranementioning
confidence: 99%
See 2 more Smart Citations
“…This is consistent with the limited calcein release from PO lipid vesicles compared with DM vesicles, [1] and supports the conclusion of Cheng et al that PO vesicles are good model membranes to study these peptides. [6] …”
Section: Aureins Target the Bacterial Membranementioning
confidence: 99%
“…[5] A more recent study with a variety of model lipid bilayers suggested a similar aurein structure in different phospholipid environments, with differences in bilayer-integration efficiency. [6] Although these studies nicely contribute to our understanding of the aurein-lipid interaction, they offer no direct insight into the in vivo antibacterial mechanism of this family of antimicrobial peptides.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…22,23 To mimic the bacterial membrane, a mixture of 1-palmitoyl-2-oleoyl-sn-glycero-3-phosphocholine (POPC) and 1-palmitoyl-2-oleoyl-sn-glycero-3-phosphoglycerol (POPG) at 1:1 molar ratio was chosen as it has been described as one of the most biologically relevant model membranes for studying the S. aureus strain. 24 ■ EXPERIMENTAL SECTION Reagents. N α -Fmoc-protected amino acids, Rink amide AM resin, and 2-(1H-benzotriazole-1-yl)-1,1,3,3-tetramethyluronium hexafluorophosphate (HBTU) for solid phase peptide synthesis (SPPS) were from NovaBiochem-EMD4Biosciences (Darmstadt, Germany).…”
Section: ■ Introductionmentioning
confidence: 99%
“…Solution CD experiments were carried out using a J-810 spectropolarimeter (JASCO, Victoria, BC, Canada) as previously described (4,16). Briefly, the spectra were obtained over a wavelength range of 185 to 250 nm using the continuous scanning mode with a response of 1 s with 0.5-nm steps, a bandwidth of 1.5 nm, and a scan speed of 20 nm/min.…”
mentioning
confidence: 99%